The mercedes coffin - Kellerman, Faye. (New York : Harper, 2008)
Fifteen years after her favorite teacher was murdered execution-style, Genoa Greeves suspects the murder of a Hollywood music producer is connected, and sets out to uncover the truth and finally close the case, even if it means putting her own life at risk.
Adult.
Adult
Keywords: Decker, Peter (Fictitious character) -- Fiction; Lazarus, Rina (Fictitious character) -- Fiction; Murder -- Fiction; Police -- Fiction; Decker, Peter (Fictional character) -- Fiction; Homicide -- Fiction; Lazarus, Rina (Fictional character) -- Fiction; Mystery fiction; Police -- Fiction; Los Angeles (Calif.) -- Fiction; Los Angeles (Calif.) -- Fiction; Mystery fiction